Habermas om teologi og filosofi: Jürgen Habermas, Auch eine Geschichte der Philosophie, 2 bd. (Bd. 1: Die okzidentale Konstellation von Glauben und Wissen. Bd. 2: Vernünftige Freiheit. Spuren des Diskurses über Glauben und Wissen). Frankfurt a. M.: Suhrkamp 2019. 1752 s. € 98 (indb.). - Nørager, Troels (Dansk Teologisk Tidsskrift, 2020)
This article seeks to give an overview and tentative evaluation of Jürgen Habermas’s most recent book, Auch eine Geschichte der Philosophie (2019). The introduction presents the author’s overall intention of providing a genealogy of post-metaphysical thinking. The first section deals with Habermas’s evolutionary perspective on religion as well as core elements of his philosophy and sociology. The second section outlines his view that the religious traditions of the so-called Axial Age have in common a tendency towards moralizing the sacred. The third section discusses Habermas’s ideas on the relation between philosophy and theology, both historically and in contemporary thought. The conclusion presents some elements of a critique while also hailing this opus magnum as an outstanding and admirable achievement.